Vestibular Rehabilitation Therapy for the Treatment of Vestibular Migraine, and the Impact of Traumatic Brain Injury on Outcome: A Retrospective Study. Issue 3 (March 2022) - Stancel-Lewis, Jack; Lau, Joanne Wai Ling; Male, Amanda; Korres, George; Rogel-Salazar, Jesus; Pavlou, Marousa; Bamiou, Doris-Eva
Abstract : Introduction: Vestibular migraine (VM) is a common condition; individuals experience dizziness with migraine symptoms. Vestibular rehabilitation therapy (VRT) has been reported as an effective treatment for VM, however, evidence is limited. VM and traumatic brain injury (TBI) can co-occur, and some suggest that TBI can induce VM. There is limited evidence on the effect a history of TBI has on VRT in patients with VM. Methods: Retrospective case series of 93 ( f  = 63, m  = 30) participants with VM and underwent VRT (mean age 48.62; SD 15.92). Pre- and post-treatment self-reported outcome measures and functional gait assessment were extracted from the participants health records and evaluated. The impact of TBI on VRT outcome in participants with VM was analyzed. Individuals with TBI and no history of migraine (n = 40) were also extracted to act as a control. Results: VRT significantly improved self-reported dizziness on the Dizziness Handicap Inventory (DHI), with a mean change of –18 points ( p  < 0.000) and +5 points on the functional gait assessment (FGA) ( p  < 0.000) in patients with VM. A history of TBI significantly impacted outcome on the DHI ( p  = 0.018) in patients with VM. VRT significantly improved all outcome measures for individuals with TBI, with a mean change of –16 points on the DHI ( p  = 0.001) and +5 points on the FGA ( p  < 0.000). VM presence significantly impacted outcome. Conclusion: VRT should be considered as a treatment option to reduce dizziness and the risk of falls in individuals with VM. TBI may negatively impact VRT outcomes in individuals with VM.